Strategi Pengelolaan Kelas dalam Pembelajaran Pendidikan Agama Islam di Madrasah Ibtidaiyah Muhammadiyah Congol - Siti Shoimah; Khuriyah, Khuriyah (Universitas Garut, 2024)
One of the key factors that influence the effectiveness of Islamic religious education (PAI) learning is classroom management strategies. The purpose of the study was to examine effective classroom management strategies in Islamic education learning at MI Muhammadiyah Congol. The research method is a qualitative case study approach. Data collection techniques were interviews, observation, and documentation. The findings of the study show that there are four aspects in effective classroom management strategies in PAI learning. These aspects include the preparation of the learning environment, the teaching approach adopted by the teacher, classroom administration management, as well as behavior control and strengthening motivation in students. Resource constraints, differences in student understanding, and limited allocation of learning time become obstacles. The results suggest expanding school support, improving teacher competence and increasing students' active participation to overcome these problems. By implementing effective classroom management strategies, it is expected to improve the quality of Islamic education learning and achieve the goals of Islamic education optimally. The implications of these findings can improve the quality of PAI learning at MI Muhammadiyah Congol and provide a foundation for further research.